On the Upper Limit of a Random Sequence and the Law of the Iterated Logarithm - Petrov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain some results concerning the upper limit of a random sequence and the law of the iterated logarithm for sums of independent random variables.